A universal platform for fabricating organic electrochemical transistors and application in biosensing technology - Cavassin, Priscila (2019)
Organic bioelectronics is a fast-rising research field that takes advantage of the soft and conducting/semiconducting nature of conjugated polymers to create devices that communicate, interface and mimic biological systems. Bioelectronics encompasses many applications, including tissue engineering, neural interfaces and biosensors. A device that has been extensively explored for such applications is the organic electrochemical transistor (OECT). The main reason is due to its amplification nature and, thus, high fidelity transducer of biological events. Additionally, OECTs convert ionic signals to electronic ones, providing a direct link between biological ion fluxes and electronics. Even though they have been widely explored in the past 10 years, a major drawback that remains unsolved is the lack of hydrophilic polymers that are suitable for applications in biological environment. Hence, in the first part of this dissertation, we propose a novel and universal OECT architecture that enables the use of virtually any type of conjugated polymer. Using the proposed method, which was based on physical chemistry principles, we successfully fabricated transistors that exhibits very high transconductance, good stability and reproducibility, using traditional water-insoluble conjugated polymers. In the second part, we developed a biosensing application using the proposed architecture. In short, the OECT device was functionalized with a cellular membrane model, making it possible to gather quantitative data on the physical and chemical properties of the membrane. This is particularly useful for understanding how different compounds interact with cells. Additionally, we were able to study the working mechanism of lidocaine, a widely used local anesthetic. The concept presented here was then successfully extended to the fabrication of biosensors, enabling thousands of water-insoluble materials that have been developed over the last several decades to be used in organic bioelectronics devices.